An applied linguistic comparison of basic and critical reading skills among EFL learners - Zayed, Niveen Mohammad (Research Journal in Advanced Humanities, 2026)
This study compared students’ competence in basic reading skills and critical reading skills. The researcher chose a reading comprehension text entitled The Buy Nothing Movement and designed ten questions to test the competence of the basic reading skills of the students and another ten questions to test the competence of their critical reading skills. The participants in this study were forty BA English language students at the Applied Science Private University, in the English Language and Translation Department. The results revealed that the students’ competence in answering the basic reading skills questions was much better than answering the critical reading skills questions; the answers to the basic questions were more complete, correct, and competent than the answers to the critical questions. In the end, the researcher recommended that English teachers must give special attention to critical reading questions while teaching reading skills.